Effectiveness of Technical Civil RHL Structure Distribution in the Lake Catchment Area Period 2021-2025 to Support The Ecosystem Resilience of Lake Limboto - Safira Putri H. Malik; Iswan Dunggio; Sukirman Rahim (West Science Interdisciplinary Studies, 2026)
Lake Limboto is one of Indonesia's national priority lakes subject to severe ecological pressure resulting from sedimentation and land-cover change within its catchment area (DTA). In response, the Watershed and Protected Forest Management Center of Bone Bolango (BPDAS Bone Bolango) implemented a Technical Civil Forest and Land Rehabilitation (RHL) program over the 2021–2025 period, constructing a total of 172 structures comprising Gully Plugs (GP), Sediment Retention Dams (DPN), Rainwater Harvesting Installations (IPAH), Infiltration Wells (SRA), and Ecohydraulic structures. This study analyzes the annual trends, proportional distribution, and functional relevance of each structure type in supporting the ecosystem resilience of Lake Limboto. Data were obtained from the BPDAS Bone Bolango Database (2026) and analyzed through annual trend tabulation, proportional analysis, and qualitative literature-based assessment. Results indicate that GPs dominated the total output at 79 units (45.93%), followed by IPAH and SRA at 34 units each (19.77%), DPN at 19 units (11.05%), and Ecohydraulic at 6 units (3.49%). Annual implementation fluctuated, peaking in 2022 (64 units) and 2024 (54 units), with complete stagnation in 2025. The combined deployment of erosion-control and water-conservation structures reflects an integrated conservation approach aimed at strengthening the hydrological and ecological resilience of the DTA. Recommendations include increasing the proportion of ecohydrological structures, integrating geospatial-based site prioritization, and ensuring program continuity beyond 2025.